Supplemental Material for: Comparison of drone ecology and behavior between Apis mellifera mellifera and the hybrid Buckfast in southwestern Sweden. - Schaumann, Finja (University of Skövde, 2024)
Most research on the biology of the western honey bee (Apis mellifera) focuses on the worker bees, but knowledge about drones is lacking despite their important role in mating with a virgin queen. Available information about their ecology and behavior are mainly based on direct observations in need of intensive experience and knowledge about honey bees. Only two recent studies conducted in France and Argentina have monitored drones continuously, but on the scale of a single observation hive or during a short time period only. Therefore, studies that have continuously monitored drone flight activity during the whole mating season are still lacking. Further, we are not aware of any studies that have compared the ecology and behavior of drones between different subspecies of Apis mellifera. Besides the aim of analysing the ecology and behavior of drones in spring and summer in Sweden, where the climate poses challenging conditions for honey bees, the objective of this project was to compare the native, but threatened, subspecies Apis mellifera mellifera (Mel) with the hybrid ’Buckfast’ (Apis mellifera x, Buck). In Sweden, the latter is most commonly used in beekeeping today.
Activity data at the entrance of the hives was collected with the use of Radio Frequency Identification (RFID) technology at two different apiaries with 8 colonies each. RFID technology enables the continuous monitoring of bees tagged with a microchip on their thorax. Hereby, only newborn drones with a maximum age of 3 days were tagged. Further, drones’ activity and behavior at the entrance of the hive was studied from video recordings. Weather parameters were measured by weather stations installed within the apiaries, enabling a direct analysis of the activity in relation to weather conditions (temperature, wind speed, rain, humidity).

Den mesta forskningen om biologin hos det västliga honungsbiet (Apis mellifera) fokuserar på arbetsbina, men kunskapen om drönarna är bristfällig trots deras viktiga roll vid parning med en jungfrulig drottning. Tillgänglig information om deras ekologi och beteende baseras huvudsakligen på direkta observationer, vilket kräver intensiv erfarenhet och kunskap om honungsbin. Endast två nyligen genomförda studier i Frankrike och Argentina har övervakat drönare kontinuerligt, men endast i form av en enda observationskupa eller under en kort tidsperiod. Därför saknas det fortfarande studier som kontinuerligt har övervakat drönarnas flygaktivitet under hela parningssäsongen. Dessutom känner vi inte till några studier som har jämfört ekologin och beteendet hos drönare mellan olika underarter av Apis mellifera. Förutom syftet att analysera ekologin och beteendet hos drönare under våren och sommaren i Sverige, där klimatet utgör en utmaning för honungsbin, var målet med detta projekt att jämföra den inhemska, men hotade, underarten Apis mellifera mellifera (Mel) med hybriden "Buckfast" (Apis mellifera x, Buck). I Sverige är det den senare som är vanligast i dagens biodling.
Aktivitetsdata vid ingången till bikuporna samlades in med hjälp av RFID-teknik (Radio Frequency Identification) i två olika bigårdar med vardera 8 bisamhällen. RFID-tekniken möjliggör kontinuerlig övervakning av bin som är märkta med ett mikrochip på bröstkorgen. Härigenom märktes endast nyfödda drönare med en maximal ålder på 3 dagar. Vidare studerades drönarnas aktivitet och beteende vid ingången till bikupan med hjälp av videoinspelningar. Väderparametrar mättes med väderstationer som installerats i bigårdarna, vilket möjliggjorde en direkt analys av aktiviteten i förhållande till väderförhållandena (temperatur, vindhastighet, regn, luftfuktighet).
Supplemental Material for: Comparison of drone ecology and behavior between Apis mellifera mellifera and the hybrid Buckfast in southwestern Sweden.
Keywords: survival; överlevnad; Species distribution; Arters utbredning; video recording; videofilmning; species-typical behavior; arttypiskt beteende; RFID; RFID; honeybees; honungsbi; Apis mellifera X; buckfastbi; Apis mellifera mellifera; nordiskt honungsbi; flight activity; flygaktivitet; buckfast bee; buckfastbi; Drones; Drönare; apis mellifera x buckfast; Natural Sciences; Naturvetenskap; Biological Sciences; Biologi; Zoology; Zoologi; Ecology; Ekologi; Behavioural Sciences Biology; Etologi; Biota; Biologi och ekologi